Dynamics and multi‐annual fate of atmospherically deposited nitrogen in montane tropical forests. (19th February 2021) - Wang, Ang; Chen, Dexiang; Phillips, Oliver L.; Gundersen, Per; Zhou, Xulun; Gurmesa, Geshere A.; Li, Shanlong; Zhu, Weixing; Hobbie, Erik A.; Wang, Xueyan; Fang, Yunting
Abstract: The effects of nitrogen (N) deposition on forests largely depend on its fate after entering the ecosystem. While several studies have addressed the forest fate of N deposition using 15 N tracers, the long‐term fate and redistribution of deposited N in tropical forests remains unknown. Here, we applied 15 N tracers to examine the fates of deposited ammonium ( NH 4 + ) and nitrate ( NO 3 ‐ ) separately over 3 years in a primary and a secondary tropical montane forest in southern China. Three months after 15 N tracer addition, over 60% of 15 N was retained in the forests studied. Total ecosystem retention did not change over the study period, but between 3 months and 3 years following deposition 15 N recovery in plants increased from 10% to 19% and 13% to 22% in the primary and secondary forests, respectively, while 15 N recovery in the organic soil declined from 16% to 2% and 9% to 2%. Mineral soil retained 50% and 35% of 15 N in the primary and secondary forests, with retention being stable over time. The total ecosystem retention of the two N forms did not differ significantly, but plants retained more 15 NO 3 ‐ than 15 NH 4 + and the organic soil more 15 NH 4 + than NO 3 ‐ . Mineral soil did not differ in 15 NH 4 + and 15 NO 3 ‐ retention. Compared to temperate forests, proportionally more 15 N was distributed to mineral soil and plants in these tropical forests. Overall, our results suggest that atmospherically deposited NH 4 + and NO 3 ‐ is rapidly lost in the short term (months) but thereafter securely retained within the ecosystem, with retained N becoming redistributed to plants and mineral soil from the organic soil. This long‐term N retention may benefit tropical montane forest growth and enhance ecosystem carbon sequestration. Abstract : 15 NH 4 + and 15 NO 3 ‐ tracers were applied to tropical montane forests to explore the fate and redistribution of atmospherically deposited N over 3 years. More than 60% of the 15 N tracer was retained within the two forests after 3 years. 15 N tracer was redistributed over time from the organic soil to plants and mineral soil.